Discontinuous Galerkin implementation of time-domain finite-element method using Crank-Nicolson scheme and complex frequency-shifted perfectly matched layers for efficient analysis of dielectric loaded waveguide structures - Ye, Z. (2014)
10.1002/mop.26349